Efficient and equitable commodity taxation: Micro-simulations based on an estimated Brazilian consumer demand system - Seki Asano; Ana Luiza Neves de Holanda Barbosa; Eduardo P. S. Fiuza (Institute for Applied Economic Research (ipea), 2015)
In this study we calculate the optimal commodity tax structure for Brazil. The micro-simulations are based on a complete demand system estimated with a flexible functional form [Almost Ideal Demand System, by Deaton and Muellbauer (1980)]. The data source is a 1995/96 national household budget survey. Preference parameters' estimates are consistent with microeconomic demand theory and allow for a highly accurate optimal commodity tax simulation. The model features the maximization of a social welfare function, subject to a balanced government budget requirement. It is assumed that the only tax policy instrument available to the government is consumption goods' and services' taxation. The trade-off between equity and efficiency is taken into account by introducing the government's aversion to inequality into the social welfare function. We also extend our analysis by allowing for a uniform per capita lumpsum payment to be made by the government to all households. Our results show that the commodity tax structure is characterized by selective tax rates. More specifically, we found that the commodities in which the lower household's expenditure classes spend most, such as food and housing, should be subsidized. As expected, the degree of selectivity is more significant for higher inequality aversion parameters. Moreover, as the tax revenue goal increases, so do all commodity tax rates. By introducing a uniform lump-sum transfer, however, this result is reversed when the central planner's degree of aversion to inequality is high enough. On the other hand, poll transfer levels are unreasonably high; when we cap them with a binding ceiling, the former pattern is restored. We believe that our empirical findings provide a valuable contribution for the current tax policy debate in Brazil, where distributive goals have a great importance in the agenda.
Keywords: 330